2020
DOI: 10.1186/s13578-020-00416-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Roles of the PI3K/AKT/mTOR signalling pathways in neurodegenerative diseases and tumours

Abstract: The PI3 K/AKT/mTOR signalling pathway plays an important role in the regulation of signal transduction and biological processes such as cell proliferation, apoptosis, metabolism and angiogenesis. Compared with those of other signalling pathways, the components of the PI3K/AKT/mTOR signalling pathway are complicated. The regulatory mechanisms and biological functions of the PI3K/AKT/mTOR signalling pathway are important in many human diseases, including ischaemic brain injury, neurodegenerative diseases, and tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
282
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(290 citation statements)
references
References 116 publications
(127 reference statements)
6
282
0
2
Order By: Relevance
“…mTOR consists of two independent functional complexes, mTORC1 and mTORC2, which can be phosphorylated to p-mTOR regulating several cellular functions, including proliferation, differentiation, tumorigenesis, angiogenesis, autophagy, and apoptosis by activating ribosome biogenesis and protein synthesis. (20,21) In our study, we found reduced CENPO expression would downregulated the expression of PIK3CA and p-mTOR, suggesting CENPO may active PI3K/AKT/mTOR signaling pathway to promote cancer progression by avoiding apoptosis and other cellarbehaviors.…”
Section: Discussionmentioning
confidence: 49%
“…mTOR consists of two independent functional complexes, mTORC1 and mTORC2, which can be phosphorylated to p-mTOR regulating several cellular functions, including proliferation, differentiation, tumorigenesis, angiogenesis, autophagy, and apoptosis by activating ribosome biogenesis and protein synthesis. (20,21) In our study, we found reduced CENPO expression would downregulated the expression of PIK3CA and p-mTOR, suggesting CENPO may active PI3K/AKT/mTOR signaling pathway to promote cancer progression by avoiding apoptosis and other cellarbehaviors.…”
Section: Discussionmentioning
confidence: 49%
“…In ovarian CSCs, ErbB4 receptor tyrosine kinase and STAT5 cooperate to promote the transcription of p85a and p110a, which are subunits of PI3K [ 16 ]. AKT is phosphorylated downstream of PI3K signaling [ 32 , 33 ], and ERK phosphorylation is enhanced by overexpression of the ErbB4 receptor [ 16 , 34 ]. The overexpressed L/T-type calcium channels increase calcium flow into the cytoplasm, which drives phosphorylation of AKT and ERK through PI3K and MAPK signaling [ 15 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of mTOR phosphorylates the downstream P70S6K1 effector to initiate the translation process and promote the synthesis of RNA and proteins (24,25). This pathway participates in the occurrence and development of multiple tumors and angiogenesis, and is also considered as the primary pathway for cancer cell survival (26,27). Then, in vitro cell experiment indicated that the transfection with PI3K/AKT/mTOR pathway agonist IGF-1 recovered the pro-apoptotic effects of PTPRZ1 overexpression.…”
Section: Discussionmentioning
confidence: 99%